Reasons for bias in ambulance clinicians’ assessments of non-conveyed patients: a mixed-methods study - Helena Johansson; Kristin Lundgren; Magnus Andersson Hagiwara (BMC Emergency Medicine, 2022)
Abstract Background The number of ambulance assignments and the influx of patients to the emergency departments (EDs) in Sweden have increased in recent years. This is one reason the protocol for prehospital emergency care was developed around referring patients for non-conveyance, either through the see-and-convey elsewhere approach or through the see-and-treat approach. However, this protocol has led to challenges in patient assessments. This study aimed to investigate the underlying causes of patient harm among those referred for the see-and-treat approach by the emergency medical services. Methods This three-phase study involved a mixed-methods design. Cases of injuries, internal investigations and incident analyses of referrals for the see-and-treat approach in two regions in south eastern Sweden from 2015 to 2020 were examined using qualitative content analysis. This qualitative analysis was the basis for the quantitative analysis of the ambulance records. After the qualitative analysis was completed, a review protocol was developed; 34 variables were used to review 240 randomly selected ambulance records logged in 2020, wherein patients were referred for the see-and-treat approach. Finally, the review results were synthesised. Results The qualitative analysis revealed three common themes: ‘assessment of patients’, ‘guidelines’ and ‘environment and organisation’. These results were confirmed by a medical journal review. Shortcomings were found in the anamnesis and in the number of targeted examinations performed. The checklist for referring patients for the see-and-treat approach and the information sheet to be provided to the patients were not used. In 34% of the ambulance records examined, the EMS clinicians deviated from the current guidelines for a see-and-treat referral. Conclusions The results indicated that the low adherence to guidelines and the patient assessment deviating from the protocol put patients at risk of being harmed during a see-and-treat referral. Measures are needed to guarantee a safe assessment of an increasing number of patients who are referred for the see-and-treat approach, especially the multi-sick elderly patients.